Three dimensional velocity structure and accurate earthquake location in Changning–Gongxian area of southeast Sichuan. Issue 2 (30th March 2020) - Long, Feng; Zhang, ZhiWei; Qi, YuPing; Liang, MingJian; Ruan, Xiang; Wu, WeiWei; Jiang, GuoMao; Zhou, LongQuan
Abstract : In order to understand the crustal structure and tectonic background of the Changning–Gongxiang area, southeastern Sichuan Province, where a series of moderate‐to‐strong earthquakes occurred in recent years, we utilized the seismic phase data both from a local dense array and from the regional seismic networks; we used the tomoDD program to invert for the high‐resolution three‐dimensional velocity structure within the depth range of 0–10 km and for accurate hypocentral locations in this area. We analyzed the seismogenic structures for the events of Xingwen M 5.7 in 2018 and Gongxian M 5.3 and Changning M 6.0 in 2019. The results show that: (1) widespread lateral inhomogeneity exists in the velocity structure of the study area, and the location of the velocity anomaly is largely consistent with known structures. In the range of distinguishable depth, the inhomogeneity decreases with increasing depth, and the velocity structure anomalies in some areas are continuous in depth; (2) earthquakes occurred in clusters, showing the characteristics of zonal folding trends in the NW‐SE and NE‐SW directions; the focal depth in the area is generally shallow in both the sedimentary cap and the crystalline basement. The seismogenic structures of small earthquake clusters are different in size and occurrence in different sections, and the clusters occurred mostly in regions with high P‐ or S‐wave velocities; (3) synthesis of a variety of data suggests that the seismogenic structures of the Xingwen M 5.7 and Changning M 6.0 earthquakes are associated with slip faults that trend NW‐SE in, respectively, the south wing and the axis of the Changning–Shuanghe anticline, while that of the Gongxian M 5.3 earthquake is associated with thrust faults that trend N‐S in the Jianwu syncline region. The dynamic sources of the three earthquakes are all from the SE pushing of the Qinghai–Tibet block on the Sichuan basin; (4) the risk of future strong earthquakes in this area must be reevaluated in light of the facts (a) that in recent years, moderate‐to‐strong earthquake swarms have occurred frequently in southeast Sichuan; (b) that the complex structural area exhibits the easy‐to‐trigger characteristic, and (c) that the small‐scale faults in this area are characterized by the phenomenon of stress "lock and release".